Nonthymoma‐associated exfoliative dermatitis in 18 cats. Issue 1 (3rd November 2014) - Linek, Monika; Rüfenacht, Silvia; Brachelente, Chiara; von Tscharner, Claudia; Favrot, Claude; Wilhelm, Sylvia; Nett, Claudia; Mueller, Ralf S.; Mayer, Ursula; Welle, Monika
<x xml:space="preserve">Abstract</x> Background Exfoliative dermatitis has been described in cats as a paraneoplastic skin disease associated with thymoma. There are anecdotal reports of cases without thymoma, with various suspected aetiologies. Hypothesis/Objectives To identify common features, underlying causes, response to therapy and outcome of nonthymoma‐associated exfoliative dermatitis in cats. Methods Retrospective analysis was carried out of cases presented to dermatology referral centres or cases submitted for histopathological examination. Detailed historical and clinical data were obtained and evaluated statistically. Histopathology was reviewed in a blinded fashion by three dermatopathologists, and PCR for herpesvirus was performed. Results Eighteen cats fulfilled all inclusion criteria. There was no sex, age or breed predisposition. All cats presented with severe generalized (77%) or multifocal exfoliation (23%); 12 cats were severely depressed. In all cats, thymoma was excluded radiographically and feline leukaemia virus tests were negative. Additional imaging procedures in 14 cats and postmortem examination in two cats did not detect neoplasia. Histopathology revealed interface dermatitis, mural interface folliculitis and sebaceous adenitis indistinguishable from findings in thymoma‐associated cases. PCR for herpes DNA was negative. No aetiology was identified. Treatment in 12 cases consisted of immunosuppressive doses of corticosteroids and/or ciclosporin; one responded to antibiotics, one to shampoo, two went into spontaneous remission, and two did not receive any therapy and were euthanized. Conclusions and clinical importance Nonthymoma‐associated exfoliative dermatitis in cats is clinically and histopathologically indistinguishable from thymoma‐associated cases. Most cases benefit from immunosuppressive therapy; therefore, an immunopathological response to an undefined trigger is suspected.